Political Party Activism Of The Malay Muslim Political Parties: Umno And Pas Grassroots Party Activists In Terengganu - Wan Rohila Ganti Wan Abdul Ghapar (Universiti Sains Malaysia, 2022)
While the general trends of political parties around the world, by contrast, show significant declines in grassroots party activism,the grassroots political party activists of PAS and UMNO in Terengganu are characterized as highly political and ideologically extreme, participating in high intensity political activities. This research explores the intensity of their activism in UMNO and PAS, and the incentives that have influenced them to become politically active since it is often taken for granted that people will only invest in political activism in exchange for some sort of benefits. This study also compares the differences of incentives that prevail among UMNO and PAS grassroots party activists. Being qualitative in nature, this study adopts the technique of in-depth interview, involving twenty -- six PAS and UMNO party activists as informants. The selection of the informants was performed using the purposive sampling method. The interview data were thematically analyzed through the content analysis method. This study finds that the informants were involved in nine high-intensity political party activities; going beyond the six high intensity political activities suggested in the literature. They generally encompassed similar types of political activities, by community and welfare programs being perennial. Combining the Rational Choice theory, the Civic Voluntarism model, the Clark-Wilson Incentives theory and the General Incentives model into a framework to understand incentives that motivate informants' political party activism, this study discovers the presence of five major incentives, namely ideology of the party, altruistic motives, entertainment values, expressive and material rewards.